2006
DOI: 10.1073/pnas.0604979103
|View full text |Cite
|
Sign up to set email alerts
|

A class of iron chelators with a wide spectrum of potent antitumor activity that overcomes resistance to chemotherapeutics

Abstract: Novel chemotherapeutics with marked and selective antitumor activity are essential to develop, particularly those that can overcome resistance to established therapies. Iron (Fe) is critical for cell-cycle progression and DNA synthesis and potentially represents a novel molecular target for the design of new anticancer agents. The aim of this study was to evaluate the antitumor activity and Fe chelation efficacy of a new class of Fe chelators using human tumors. In this investigation, the ligands showed broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
667
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(710 citation statements)
references
References 33 publications
38
667
3
2
Order By: Relevance
“…Chelators are widely investigated because of their therapeutic potential in the treatment of metal overload and diseases related to imbalanced metal homeostasis including hemochromatosis, β-thalassemia, Alzheimer's or Parkinson's diseases and cancer [8,9,12,70].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chelators are widely investigated because of their therapeutic potential in the treatment of metal overload and diseases related to imbalanced metal homeostasis including hemochromatosis, β-thalassemia, Alzheimer's or Parkinson's diseases and cancer [8,9,12,70].…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, increased glycolysis compensates for the higher energy demand created by the "futile cycling" of the transporter [79,81,82], but the oxidative stress associated with oxidative phosphorylation ultimately results in the selective apoptosis of MDR cells [83]. ROS have not only been implicated in the paradoxical sensitivity of resistant cells, but also in the mechanism of toxicity of chelators [8,12,13].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiosemicarbazone-related compounds are well-known to have active antiviral, antibacterial, antimalarial, and antihypertensive properties (42), as well as antitumor activity that can overcome resistance to chemotherapeutics (19,43). Recently, we reported that the small-molecule thiosemicarbazone NSC73306 is significantly more cytotoxic to cells that overexpress P-glycoprotein than to cells that do not, and this unique property is directly proportional to functional P-glycoprotein protein expression (19).…”
Section: Discussionmentioning
confidence: 99%
“…Many cancers exhibit an increased requirement for iron, presumably because of the need for iron as a cofactor in proteins essential to sustain growth and proliferation (13). Modulation of iron-regulatory proteins affects growth of lung tumor xenografts (4, 5), and agents that deplete iron are currently under investigation as anticancer therapies (69). …”
Section: Introductionmentioning
confidence: 99%